1975
DOI: 10.1021/bi00676a014
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of steroids with nucleic acids

Abstract: 17beta-Estradiol and testosterone bind to both native and denatured DNA, and to RNA and poly(A)-poly(U). Binding affinity depends on the conformation of nucleic acid. Lowering the electrolyte concentration and raising the temperature increase the binding of 17beta-estradiol to native DNA and decrease that to denatured DNA. In 0.01 M NaCl and at 37 degrees, more 17beta-estradiol is bound to native DNA than to denatured DNA. Higher binding of steroid to denatured DNA relative to native DNA at low temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…ethanol was added. The DNA was spooled out of the mixture, dissolved in TNE and digested with RNase, followed by digestion with Pronase (Arya & Yang, 1975;Arya, i981). The solution was again extracted with phenol :chloroform :isoamyl alcohol followed by extraction with ether.…”
Section: Methodsmentioning
confidence: 99%
“…ethanol was added. The DNA was spooled out of the mixture, dissolved in TNE and digested with RNase, followed by digestion with Pronase (Arya & Yang, 1975;Arya, i981). The solution was again extracted with phenol :chloroform :isoamyl alcohol followed by extraction with ether.…”
Section: Methodsmentioning
confidence: 99%
“…This immediately leads us to the interaction of steroids with DNA, the main target for transcriptional Although some reports are available on the binding of steroids to DNA [16][17][18] the biological relevance of this interaction is not known [7]. The steroid-DNA binding hypothesis was refuted by the observed in vitro binding of the receptor to W R E [ 19,201. However, in vivo studies showed the mandatory presence of steroids for receptor-HE interaction [21].…”
Section: Introductionmentioning
confidence: 99%